Christopher Robin [videorecording (DVD)] - Forster, Marc, 1969-; McGregor, Ewan, 1971-; Atwell, Hayley, 1982-; Carmichael, Bronte; Milne, A. A. (Alan Alexander), 1882-1956; Shepard, Ernest H. (Ernest Howard), 1879-1976 (Walt Disney Studios Home Entertainment, 2018)
Christopher Robin, now a working man with a family in London, unexpectedly encounters his childhood friend, Winnie-the-Pooh, and their friends from the Hundred Acre Wood.